Effect of metal ions and chemical agents on the activity of endoglucanase GH5 exploited from goats-rumen bacterial metagenomic DNA data - Khanh Hoang Viet, Nguyen; Thuy Hoa, Ha Thi; Nam Hai, Truong; Thi Huyen, Do (Vietnam Journal of Biotechnology, 2021)
A gene coding for GH5 endoglucanase exploited from metagnomic DNA data of bacteria in Vietnamese goats’ rumen was modularity structure including a catalytic module, a fibronectin-3 like module and an X module. The recombinant enzyme was sucessfully expressed in E. coli and purified.  To study the effect of some metal ions and chemicals on enzyme activity, in this study, we used some tools including Swiss-Prot, ProFunc, COFACTOR for prediction of enzyme structure and ligands interaction. The obtained results indicated that the most similar structure with enzyme had two conserved residues (Asp-190 và Asp-192) linked with Mn2+ within a radius of ~ 3.5 Å from the center of ion Mn2+ and enzyme molecule contained a disulphide bond. Experimental results for essessment of the effect of some metal ions (Ca2 +, Mn2 +, Mg2+, Ni2+, K+, Co2+, Cu2+, Zn2+, Fe3+) at the final concentration of 10 mM and of six common chemicals including SDS (1%), urea (1 µM), 2-mercaptoethanol (1 µM), EDTA (1 µM), tween 80 (1mM), triton X-100 (1 µM) showed that only Mn2+ increased enzyme activity slightly at concentration of 10 mM and two times at the concentration of 40 mM Mn2+. The Mn2+ has been identified as a specific binding agent may increase the stability and activity of endoglucanase GH5.